Oven Listrik Keripik Buah Berbasis Arduino dengan Menggunakan Metode Fuzzy Logic dan Sensor DHT22 - Achmad Ridwan (AI Society & STMIK Indonesia, 2024)
Small-scale fruit chip production faces challenges in maintaining optimal temperature and humidity during the drying process. This research develops the Endull Kripps electric oven using Arduino-based fuzzy control technology and DHT22 sensors to address these issues. The aim is to design an efficient oven system that produces high-quality chips. The Research and Development method was applied in system design and testing. Results show up to 95% increase in energy efficiency compared to conventional methods. The chips produced have 1.5% lower moisture content, crispier texture, and higher organoleptic scores. The system maintains temperature stability with high accuracy, demonstrating significant potential in optimizing food drying processes. This innovation supports the Merdeka Belajar Kampus Merdeka program by providing a platform for students to develop entrepreneurial skills in the context of the food industry.